URGENSI LEGALITAS USAHA BAGI USAHA MIKRO, KECIL DAN MENENGAH (UMKM) DI KABUPATEN OGAN KOMERING ULU - Inti Pitasari; Ahmad Albarokah; Ariansyah; Delta Alkia; Dini Mey Bella; Dwi Setianingsih; Husna Laela; Khoirul Umam; Khoirotun Nisa; Nazua Lidiyani; Nova Haryanti; Wahida Salsabila; Wika Saputri (JURNAL ILMIAH EDUNOMIKA, 2026)
Business legality is a license that must be owned by all business actors. Where the legality of this business will be a legal protection for business actors. So that the management of business legality is needed by business actors. This writing aims to find out the legal regulations related to legality and urgency related to business legality. This study was written using empirical legal research methods using a qualitative approach. In the process of writing the data sources are primary data, namely the results of interviews and secondary data, namely library research. The results of the study show that business legality is very important for business actors. As stated in Article 10 of Law Number 3 of 2014 concerning Industry, it is stated that every industrial business activity must have an industrial business license. Therefore, business legality is very important for business actors because this business license can be a legal protection for business actors.